EVALUASI SISTEM PENGOLAHAN LIMBAH CAIR DOMESTIK PADA GEDUNG ADMINISTRASI DI PT.X - Hafis Dias Gitara; Hardoyo Hardoyo; Sulastri Sulastri (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The Domestic Wastewater Treatment Plant (IPAL) plays a crucial role in maintaining environmental quality, especially within industrial operation areas. This study aims to evaluate the domestic wastewater treatment system at the Administration Building of PT.X. The research method includes direct observation, document analysis, and laboratory testing of water quality parameters such as BOD, COD, TSS, pH, and oil & grease content. The IPAL system combines anaerobic and aerobic processes, supported by an activated carbon filtration stage. The evaluation results indicate that the treatment system effectively reduces key pollutants to levels that comply with the quality standards set by the Indonesian Ministry of Environment and Forestry Regulation No. 68 of 2016. The achieved treatment efficiency demonstrates the system's success in managing domestic wastewater in a sustainable and environmentally friendly manner.